0
$\begingroup$

I would like to prove the distribution of $S_n$ being the sum of $X_n$ Poisson distributed with mean $\mu$ is the sum of the means of the individual distribution, as stated by @Brian Tung in a comment, in this question it is calculated by the convolution of two independent Poisson distributions. So my try:

The pdf of a Poisson distribution is:

$$ \displaystyle P(X_n = k) = e^{-\mu} \frac{\mu^k}{k!}, \; \; k = 0,1,\dots $$

The Convolution of a function is defined as:

$$ \displaystyle (f \star g)(t) = \int_{-\infty}^{\infty} f(\tau)g(t-\tau) d \tau $$

Then applying this here get:

$$ \displaystyle P(S_n = k) = (P(S_n = \tau) \star P(S_n = \tau))(t) = \int_{-\infty}^{\infty} e^{-\mu} \frac{\mu^{\tau}}{\tau!} e^{-\mu} \frac{\mu^{\tau - t}}{(\tau-t)!} d \tau $$

$$ \displaystyle = \int_{-\infty}^{\infty} \frac{e^{-2 \mu} \mu^{-t}}{\Gamma (\tau+1) \Gamma (\tau-t+1} d\tau $$

And I'm totally stuck .. I think i haven't even started this correct?


Continuing from @echzhen's answer:

$$ \displaystyle = \sum_{i=0}^{k} e^{\lambda_2} \frac{\lambda_2^{k-i}}{(k-i)!} e^{\lambda_1} \frac{\lambda_1^{i}}{(i)!} $$

$$ \displaystyle = e^{\lambda_1 + \lambda_2} \sum_{i=0}^k \frac{1}{k!} \frac{k!}{(k-i)!(i)!} \lambda_1^i \lambda_2^{k-i} $$

Can we bring the $1/k!$ out infront of the sum? If so, then we apply the binomial theorem:

$$ \displaystyle = e^{\lambda_1 + \lambda_2} \frac{1}{k!} \sum_{i=0}^k {k \choose i} \lambda_1^i \lambda_2^{k-i} $$

$$ \displaystyle = e^{\lambda_1 + \lambda_2} \frac{1}{k!} (\lambda_1 + \lambda_2)^{k} $$

$\endgroup$
  • $\begingroup$ First notice, that if you proved that $X_1 + X_2$ is Poisson with $\lambda = \lambda_1 + \lambda_2$ you can extend this result to any finite sum. $\endgroup$ – echzhen Feb 24 '16 at 19:55
  • $\begingroup$ I added this proof, is it correct? .. although I only made this step because I know what the conclusion should be, how can I know before hand to plug in $\mu_1 + \mu_2$ into where the mean goes? $\endgroup$ – Sunhwa Feb 24 '16 at 20:02
  • $\begingroup$ On the one hand it is correct to put $\mu_1+\mu_2$, but on the other hand it is not a proof :) $\endgroup$ – echzhen Feb 24 '16 at 20:05
  • $\begingroup$ I am still interested in seeing the proof using convolutions .. but it must be beyond me, as I had trouble with this proof for $n=2$ >.< maybe in a couple years $\endgroup$ – Sunhwa Feb 24 '16 at 20:31
  • $\begingroup$ Don't you think that with convolution the proof is basically the same? Just compare the sum that you have obtained and the integral. $\endgroup$ – echzhen Feb 24 '16 at 20:37
1
$\begingroup$

Let $X_1, X_2$ be independent Poisson random variables with intensity $\lambda_1, \lambda_2$ respectfully. Let $S = X_1+X_2$, hence $$P\{X_1+X_2 = k\}=\sum\limits_{i=0}^{\infty}P\{X_1+X_2=k|X_1=i\}P\{X_1 = i\} =\sum\limits_{i=0}^{k}P\{X_2=k-i\}P\{X_1 = i\}$$ can you go from here?

$\endgroup$
  • $\begingroup$ How can you fix the sum finite in the last step here? .. because you first fix $X_1$ then $X_2$? $\endgroup$ – Sunhwa Feb 24 '16 at 20:32
  • 1
    $\begingroup$ Because $P\{X_2 < 0\} = 0$ $\endgroup$ – echzhen Feb 24 '16 at 20:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.